Kompos Cair sebagai Alternatif Pupuk yang Ramah Lingkungan dalam Produksi Padi - Siti Mudmainah; Dwi Ari Cahyani; Purwanto Purwanto (Universitas Sebelas Maret, 2019)
The development of cheap and easily applied organic fertilizer technology through extraction of fertilizers into liquid organic fertilizer has become one of the simple and inexpensive technological alternatives. The variety of raw materials for making liquid compost will certainly affect nutrient content and useful microbial content. This study was aimed to examine the effect of compost tea from various compost sources enriched with biological agents to improve the growth and yield of rice plants that are cultivated organically. This study used Randomized Complete Block Design with 10 treatments and repeated three times. The treatments tried included p0: control; p1: liquid compost from cow compost; p2: liquid compost from chicken coop compost; p3: liquid compost from mushroom waste; p4: liquid compost from cow compost + Pseudomonas flouresence; p5: liquid compost from compost chicken coop + Pseudomonas flouresence; p6: liquid compost from waste mushroom + Pseudomonas flouresence; p7: liquid compost from cow compost + Trichoderma harzianum; p8: compost tea from chicken coop compost + Trichoderma harzianum; p9: liquid compost from waste of mushroom + Trichoderma harzianum. The variables observed included plant height, number of tillers, leaf greenness, leaf area, LAI, number of productive tillers, panicle length, number of seeds per panicle, percentage of filled grain, and grain yield. The results showed that the application of liquid compost enriched with useful microorganisms had not shown its effect in increasing the growth and yield of Sintanur variety in organic cultivation. The highest yield were achieved in the treatment of liquid compost from baglog mushroom enriched with Trichoderma harzianum at 3.06 tons ha-1.